PENGETAHUAN KEAMANAN PANGAN PENJUAL MAKANAN JAJANAN DI LINGKUNGAN SEKOLAH KELURAHAN WONODRI KECAMATAN SEMARANG SELATAN KOTA SEMARANG Knowledge of Food Security of The Street Food Eat Sellers in School Country Side of Wonodri Subdistrict of South Semarang - Siti Aminah; Nur Hidayah (JURNAL LITBANG, 2006)
Abstract Case of Food poisoned progressively mount as long as 2004, one of factor is less awake of food security. Research in general aim to lvtow lcnowledge about food security all seller of environmental food street food of school This research [conducted] at school which reside in region of village of Wonodri. Grand total of Obyek there is 7, The total of 17 selles streed fool are selected as samples. Used by appliance is Queisioner about security offood and practice of hygiene and sanitasi Result Of Research indicate that in general sample have htowledge offood security with good category as much: 17,65 gratuity medium 52,94 gratuity and less 29,41 gratuity Keyword : lmowledge, food security and street food